2022
DOI: 10.1126/sciadv.abn7162
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled siRNA nanoparticles targeting IL11 inhibit lung fibrosis and improve pulmonary function post-bleomycin challenge

Abstract: Interleukin-11 (IL-11) is a profibrotic cytokine essential for the differentiation of fibroblasts into collagen-secreting, actin alpha 2, smooth muscle–positive (ACTA2 + ) myofibroblasts, driving processes underlying the pathogenesis of idiopathic pulmonary fibrosis (IPF). Here, we developed an inhalable and mucus-penetrative nanoparticle (NP) system incorporating siRNA against IL11 (si IL11 @PPGC NPs) and investigated therapeutic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 57 publications
(59 reference statements)
2
37
0
Order By: Relevance
“…Tissue images indicated that there was no AA3-DLin LNP induced inflammation detected after comparison with PBS control groups (Figure S8 and S9). …”
Section: Resultsmentioning
confidence: 99%
“…Tissue images indicated that there was no AA3-DLin LNP induced inflammation detected after comparison with PBS control groups (Figure S8 and S9). …”
Section: Resultsmentioning
confidence: 99%
“…However, many of the original insights into IL11 biology were based on the use of rhIL11 in the mouse, which has unexpected effects [ 7 , 8 ]. This realization underpins the discovery that IL11 is profibrotic [ 4 , 5 , 6 , 9 , 11 ], whereas the earlier literature had reported it as anti-fibrotic [ 3 , 40 , 41 , 42 ]. We suggest that, as it was for fibrosis, the role for IL11 in inflammation has been misinterpreted.…”
Section: Discussionmentioning
confidence: 99%
“…However, species-matched IL11 was recently found to have ERK-dependent pro-fibrotic activity in fibroblasts [ 4 , 5 , 6 , 7 ], and it transpires that rhIL11 has unexpected activity in the mouse and paradoxically inhibits endogenous murine IL11 [ 8 ]. In mammals, IL11 is now largely accepted to be pro-fibrotic [ 9 ] and is increasingly viewed as anti-regenerative [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many of the original insights into IL11 biology were based on the use of rhIL11 in the mouse, which has unexpected effects [7,8]. This discovery underpins the realization that IL11 is profibrotic [46,9,11] whereas the earlier literature had reported it as anti-fibrotic [3,3941]. We suggest that, as it was for fibrosis, the role for IL11 in inflammation is misinterpreted.…”
Section: Discussionmentioning
confidence: 96%
“…However, species matched IL11 was recently found to have ERK-dependent pro-fibrotic activity in fibroblasts [4][5][6][7] and it transpires that rhIL11 has unexpected activity in the mouse and inhibits endogenous murine IL11 [8]. In mammals, IL11 is now largely accepted to be pro-fibrotic [9] and is increasingly viewed as anti-regenerative [8,10,11].…”
Section: Introductionmentioning
confidence: 99%